Altered response to risky decisions and reward in patients with obsessive–compulsive disorder - Moreira, Pedro Silva (2020)
Background: Patients with obsessive–compulsive disorder (OCD) employ ritualistic behaviours to reduce or even neutralize the anxiety provoked by their obsessions. The presence of excessive rumination and indecision has motivated the view of OCD as a disorder of decision-making. Most studies have focused on the “cold,” cognitive aspects of decision-making. This study expands current understanding of OCD by characterizing the abnormalities associated with affective, or “hot” decision-making. Methods: We performed a functional MRI study in a sample of 34 patients with OCD and 33 sex-and age-matched healthy controls, during which participants made 2-choice gambles taking varying levels of risk. Results: During risky decisions, patients showed significantly reduced task-related activation in the posterior cingulum, lingual gyrus and anterior cingulate cortex. We identified significant group × risk interactions in the calcarine cortex, precuneus, amygdala and anterior cingulate cortex. During the outcome phase, patients with OCD showed stronger activation of the orbitofrontal cortex, anterior cingulate cortex and putamen in response to unexpected losses. Limitations: The group of patients not receiving medication was very small (n = 5), which precluded us from assessing the effect of medication on risk-taking behaviour in these patients. Conclusion: Obsessive–compulsive disorder is associated with abnormal brain activity patterns during risky decision-making in a set of brain regions that have been consistently implicated in the processing of reward prediction errors. Alterations in affective “hot” processes implicated in decision-making may contribute to increased indecisiveness and intolerance to uncertainty in patients with OCD.